Pengaruh Nostalgia, Relaksasi, Atraksi, Dan Wisata Halal Terhadap Daya Tarik Wisatawan (Studi Kasus Wisata Tradisional Pasar Kamu (Karya Anak Muda) Desa Denai Lama Kec. Pantai Labu) - Nur Afria Nanda Safitri; Fauzi Arif Lubis (Jurnal Ilmiah Ekonomi Islam, 2023)
Tourism is an industry that is able to provide economic growth both in terms of employment opportunities, income, standard of living of the people, one of the tourism industries in Indonesia, namely Youth Week Tours (KAMU) located in the Kampoeng Lama Tourism Village, Denai Lama Village, Dusun II Kec. Kab. Pantai Labu. Deli Serdang, North Sumatra. The purpose of this study is to see how the influence of Nostalgic, Relaxation, Attraction, Halal Tourism on Tourist Attraction. The research sample is 100 people. This study uses Observation and Questionnaire methods. The author observed the variables Nostalgic (X1), Relaxation (X2), Attraction (X3), Halal Tourism (X4) and Tourist Attraction (Y). This data was tested using classical assumption testing, hypothesis testing, concurrent test (F test) and partial test (t test). This research used quantitative descriptive analysis with multiple linear regression assisted by IBM SPSS version 25.0 software. and the Attraction variable has a positive and significant effect on the attractiveness of tourists visiting the Karya Anak Muda (KAMU) weekend tour. However, the Relaxation and Halal Tourism variables have no effect on tourist Attraction. Simultaneously Nostalgic, Relaxation, Attraction, Halal Tourism have a significant effect on tourist Attraction.